1987
DOI: 10.1007/bf01974936
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostaglandin biosynthesis by etodolac. I. Selective activities in arthritis

Abstract: Etodolac is the first anti-inflammatory drug belonging to the tetrahydropyranoindole class. In contrast to several other common anti-inflammatory drugs, etodolac exhibited an unusually high potency as an inhibitor of established adjuvant arthritis relative to its activity against carrageenan paw edema in the rat. This phenomenon led us to investigate whether the ability of NSAIDs to inhibit prostaglandin biosynthesis differed between cultures of macrophages, which are present in inflammatory exudates, and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Etodolac has been shown to inhibit PGE 2 biosynthesis by macrophages, but is even more effective in inhibiting PGE 2 biosynthesis by chondrocytes and synoviocytes [12]. That etodolac is effective as a treatment for OA is demonstrated in the controlled double-blind data reviewed here: etodolac is clearly more efficacious than placebo and is comparable to aspirin, diclofenac, piroxicam, and naproxen [5][6][7][8].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Etodolac has been shown to inhibit PGE 2 biosynthesis by macrophages, but is even more effective in inhibiting PGE 2 biosynthesis by chondrocytes and synoviocytes [12]. That etodolac is effective as a treatment for OA is demonstrated in the controlled double-blind data reviewed here: etodolac is clearly more efficacious than placebo and is comparable to aspirin, diclofenac, piroxicam, and naproxen [5][6][7][8].…”
Section: Discussionmentioning
confidence: 88%
“…Etodolac readily penetrates synovial fluid [18], and is a potent inhibitor of prostaglandin synthesis [12], but does not inhibit production of IL-1. Therefore, one might expect increased cartilage damage during treatment with etodolac.…”
Section: Discussionmentioning
confidence: 99%
“…Bone resorption was somewhat attenuated even at the lower drug concentrations tested, possibly reflecting a PGE/-dependent contribution to the total response which accounts for IL-1 stimulation of bone resorption. The concentration dependence of etodolac inhibition of PGE 2 accumulation in calvarial cultures is in accord with the concentrations required to inhibit PGE~ biosynthesis in other connective tissue cells, such as synoviocytes and chondrocytes [14]. Other cyclooxygenase inhibitors have demonstrated the ability to inhibit bone resorption in vitro [23].…”
Section: Discussionmentioning
confidence: 93%
“…Bones were incubated for an additional 72 h, then bones and culture medium were assessed for 4SCa content. The PGE 2 content of some cultures was determined with an ELISA [14].…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Its therapeutic effects are due to its ability to inhibit prostaglandin synthesis. It is indicated for relief of signs and symptoms of rheumatoid arthritis and osteoarthritis 7 . A recent clinical trial demonstrated that etodolac was effective in improving rear limb function in dogs with chronic osteoarthritis secondary to hip dysplasia 8 .…”
Section: Introductionmentioning
confidence: 99%